Development of a Crowd-Stress Index (CSI) for use in risk assessment - Parsons, K.; Mohd Mahudin, Nor Diana (Taylor & Francis, 2009)
A Crowd Stress Index for use in risk assessment was developed in four parts: a literature review to identify relevant factors and understand the terms 'crowd' and 'crowding'; a study on an underground train; personal interviews; and a climatic chamber experiment in which physiological and subjective measures were taken from people in a crowd. Eight components were identified; physical, social, personal, crowd characteristics, crowd dynamics, crowd behaviour, location, and psychological. Ninety-two questions in a risk assessment questionnaire provide the data for scores on 42 themes, leading to scores on the eight components in terms of contribution to crowd stress and finally as single index value ranging from ‘no crowd stress’ to ‘extremely high crowd stress’. The index appears sufficiently well developed for validation in practical applications.